Assessment of Motor Vehicle Repair Shop Service Quality Perception Using the SERVPERF Model and Lean Service - Mega Cattleya PA Islami; Rizqi Novita Sari; Sinta Dewi; Isna Nugraha; Yekti Condro Winursito; Hafid Syaifullah (UNIPA PRESS, 2023)
The benchmark for the success of a business or product is to measure the satisfaction of customers who have used or felt the goods or services. The customer's expectations of the function and emotional happiness factors that arise from the use of goods or services are entirely the responsibility of the producer. So that manufacturers need to focus on what attributes must be presented in a product or service to increase customer satisfaction. The decrease in customer interest in providing vehicle service at an automotive company in Sidoarjo is the problem studied in this study, to analyze the level of customer satisfaction and attributes that are priority improvements as recommendations for the company. Data generated from customers is processed and analyzed using the Service Performance (SERVPERF) and Lean Service methods. Based on the results of data processing, it can be concluded that the level of customer satisfaction with service quality is 82.3%, and three service attributes are classified as a top priority and two types of critical waste.